Syntheses and crystal structures of a new family of hybrid perovskites: C5H14N2·ABr3·0.5H2O (A = K, Rb, Cs) - Sarah Ferrandin; Alexandra M. Z. Slawin; William T. A. Harrison (Acta Crystallographica Section E: Crystallographic Communications, 2019)
The syntheses and crystal structures of three hybrid perovskites, viz. poly[1-methylpiperizine-1,4-diium [tri-μ-bromido-potassium] hemihydrate], {(C5H14N2)[KBr3]·0.5H2O}n, (I), poly[1-methylpiperizine-1,4-diium [tri-μ-bromido-rubidium] hemihydrate], {(C5H14N2)[RbBr3]·0.5H2O}n, (II), and poly[1-methylpiperizine-1,4-diium [tri-μ-bromido-caesium] hemihydrate], {(C5H14N2)[CsBr3]·0.5H2O}n, (III), are described. These isostructural (space group Amm2) phases contain a three-dimensional, corner-sharing network of distorted ABr6 octahedra (A = K, Rb, Cs) with the same topology as the classical perovskite structure. The doubly protonated C5H14N22+ cations occupy interstices bounded by eight octahedra and the water molecules lie in square sites bounded by four octahedra. N—H...Br, N—H...(Br,Br), N—H...O and O—H...Br hydrogen bonds consolidate the structures.